Tuberculosis practices among private medical practitioners in Kaski district, Nepal - Nepal, AK; Shrestha, A; Baral, SC; Bhattarai, R; Aryal, Y (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Although the evidences suggest that more than one third tuberculosis (TB) cases are being managed in private sector, the quality of care in private sector is major concern. However, the information regarding the private practices were lacking. Therefore the study was conducted to gain insights on current practices of TB management at private sectors. MATERIALS AND METHODS: A descriptive cross sectional study, applying quantitative method, was conducted at two cities of Kaski among all private practitioners, private pharmacies and private laboratories through self administered questionnaire and structured interview schedule. RESULTS: Nearly one fourth of the TB suspects in the district were found to have consulted private providers with about 20.0% of the total smear positive cases diagnosed in private laboratories. Beside sputum microscopy, Private Medical Practitioners (PMPs) were also found to prefer other tests like X-ray, culture for TB diagnosis. Similarly, PMPs’ varying prescription of anti TB drugs beyond National TB Programme (NTP) recommendation along with their weak recording and case holding were noteworthy, and the cost of TB treatment seemed higher in private sector. Only one third of private institution had their staff trained in TB. Except some informal linkage, no collaboration between public and private sector was noted. CONCLUSIONS: Private sector was managing many TB cases in the district. However, their practice of TB management was not much satisfactory. Therefore NTP should take effective measures for Public Private Mix and to make them aware of the standards through training and orientation in order to improve the quality of care. DOI: http://dx.doi.org/10.3126/ijim.v1i2.7085 Int J Infect Microbiol 2012;1(1):68-75